Faktor-Faktor yang Berhubungan dengan Kecemasan Pasien Pre Operasi Seksio Sesarea di Rumah Sakit Umum Handayani Kotabumi - Bramita, Yosica; Astuti, Titi; Murhan, Al (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT The average case of cesarean section in the world is around 5-15% per 1000 births in the world. In Indonesia, the incidence of cesarean section has increased, namely 80% of births are by cesarean section with an average of 17.6% of 78,736 births. In Lampung province in 2018 cases of cesarean section were around 13.2% of 2,644 births. At the Handayani Kotabumi General Hospital in 2020 there were 518 caesarean sections out of a total of 712 deliveries or (72.7%). Anxiety can be experienced by pre-cesarean section mothers because surgery is a potential or actual threat to a person's integrity that can evoke physiological and psychological stress reactions.The aim of this study was to determine the factors associated with the level of anxiety in preoperative cesarean section patients at Handayani Kotabumi General Hospital. Type of quantitative research with analytic survey design and cross sectional approach. The sampling technique uses a purposive sampling technique, a sample of 33 respondents. Time of study June 6-June 25 2022. Statistical tests using the Chi-Square test. The results showed that the majority of respondents experienced moderate anxiety (57.6%). Statistical test results obtained at age p-value (0.011) < α (0.05), education p-value (0.001) < α (0.05), parity p-value (0.002) < α (0.05), and husband's support p-value (0.004) < α (0.05). It can be concluded that there is a relationship between age, education, parity, husband's support and the anxiety of patients with preoperative cesarean section. Researchers hope that the factors associated with the anxiety of preoperative cesarean section patients can be considered so that various kinds of complications do not occur during the perioperative period. Keywords: Factors, Anxiety, Cesarean Section  ABSTRAK Kasus rata-rata seksio sesarea di dunia sekitar 5-15% per 1000 kelahiran di dunia. Di Indonesia angka kejadian seksio sesarea mengalami peningkatan, yaitu 80% metode persalinan dengan seksio sesarea dengan rata rata 17,6% kasus seksio sesarea dari 78.736 kelahiran. Di provinsi Lampung tahun 2018 kasus seksio sesarea sekitar 13,2% dari 2.644 kelahiran. Di Rumah Sakit Umum Handayani Kotabumi tahun 2020 seksio sesarea sebanyak 518 orang dari total 712 persalinan atau sebesar (72,7%). Kecemasan dapat dialami oleh ibu pre seksio sesarea karena tindakan pembedahan merupakan ancaman potensial maupun aktual pada integritas seseorang yang dapat membangkitkan reaksi stres fisiologis maupun psikologis.Tujuan penelitian ini untuk mengetahui faktor-faktor yang berhubungan dengan tingkat kecemasan pada pasien pre operasi seksio sesarea di Rumah Sakit Umum Handayani Kotabumi. Jenis penelitian kuantitatif dengan rancangan survey analitik dan pendekatan cross sectional. Teknik sampling menggunakan teknik purposive sampling, sampel sebanyak 33 responden. Waktu penelitian pada 6 Juni- 25 Juni 2022. Uji statistik menggunakan uji Chi-Square.  Hasil penelitian didapatkan mayoritas responden mengalami kecemasan sedang sebanyak (57,6%). Hasil uji statistik diperoleh pada usia p-value (0,011) < α (0,05), pendidikan p-value (0,001) < α (0,05), paritas p-value (0,002) < α (0,05), dan dukungan suami p-value (0,004) < α (0,05). dapat disimpulkan ada hubungan antara usia, pendidikan, paritas, dukungan suami dengan kecemasan pasien pre operasi seksio sesarea. Peneliti berharap agar faktor faktor yang berhubungan dengan kecemasan pasien pre operasi seksio sesarea dapat diperhatikan supaya tidak terjadi berbagi macam komplikasi selama periode perioperatif. Kata Kunci: Faktor-Faktor, Kecemasan, Seksio Sesarea